Respuesta :

Answer:

The solution is [tex]x=-1,\ y=-2,\ and\ z=0[/tex]

Step-by-step explanation:

Given:

The system of equations given are:

[tex]x-y+z=1\\x+y+3z=-3\\2x-y+2z=0[/tex]

Add first and second equations. This gives,

[tex]x-y+z+x+y+3z=1-3\\2x+4z=-2\\\textrm{Divide both sides by 2}\\x+2z=-1-----\ 4[/tex]

Adding equations 2 and 3, we get

[tex]x+y+3z+2x-y+2z=-3+0\\3x+5z=-3 --------------\ 5[/tex]

We need solve equations 4 and 5.

Multiplying equation (4) by -3, we get

[tex](x+2z=-1)\times -3=-3x-6z=3[/tex]

Adding the above equation to equation (5), we get

[tex]-3x-6z+3x+5z=3-3\\-z=0\\z=0[/tex]

Now, we plug in [tex]z=0[/tex] in equation (4). This gives,

[tex]x+2(0)=-1\\x+0=-1\\x=-1[/tex]

Now, we plug in [tex]x=-1,z=0[/tex] in equation (1). This gives,

[tex]-1-y+0=1\\-1-y=1\\-y=1+1\\-y=2\\y=-2[/tex]

Therefore, the solution is [tex]x=-1,\ y=-2,\ and\ z=0[/tex]